Kinds and Functions of Maxim Politeness in The Kelly Clarkson Show - Buha Nisa H Tampubolon; Rahmadsyah Rangkuti; Ely Hayati Nasution (LingPoet: Journal of Linguistics and Literary Research, 2021)
This article aims to discuss the kinds and functions of some maxim of politeness which is used in The Kelly Clarkson Show. Two theories are used in doing this research , the first ist theory proposed by Leech Principles of Pragmatics (1983) and the second is a theory proposed by Searle Speech Event (1979). In doing this reseacrch the writer uses descriptive and qualitative by Miles, Huberman and Saldana (2004) to analyze the research. The source of data in this thesis taken from the YouTube videos The Kelly Clarckson Show. The data are the utterances of the host and the guests in the videos. The finding of this research shows that there are three kinds of the maxim which are used in these videos they are Approbation, Agreement, and Modesty Maxim. The most dominant maxim found is the Approbation maxim. Then, there were two kinds of functions of the maxim of politeness found in The Kelly Clarckson Show, they are convivial and collaborative.